Development of Single-Longitudinal-Mode Selection Technology for Solid-State Lasers - Xuanpu Zhang; Zhihan Wang; Shi Liu; Siyu Gou; Rong Fan; Duo Jin; Zhenao Bai; Zhenxu Bai (International Journal of Optics)
Lasers with narrow linewidths and single frequencies are widely used in fields such as radar detection, nonlinear optics, and precision measurements. The demand for such lasers has promoted the rapid development of single-longitudinal-mode (SLM) selection technology. Here, we highlight the working principles of current mainstream SLM selection technologies and the recent advances in the field. We compare the characteristics of different SLM selection methods and list the challenges faced by these technologies.